The journalistic coverage of the wildfires in the Spanish digital press: the case of Galicia 2017 - Delgado Arango, Natalia; Vicente Mariño, Miguel (Revista Española de Comunicación en Salud, 2019)
Introduction: The wave of wildfires in the autumn season of 2017, that claimed the lives of 45 people in Portugal and four in Galicia, brought up the big challenge to the media of provide immediate and qualitative information in disaster situations. Objectives: Determine the digital press priorities in Spain reporting about wildfires, explain news coverage and provide recommendations from a journalistic perspective. Methods: Quantitative and qualitative analysis of press articles about wildfires in Galicia in 2017 published as digital editions in EL País and La Voz de Galicia from October 13th to 23rd of 2017. Results: Both media give priority to the use of governmental sources and a single point of view. El País provide more balanced information in terms of topics and frames. La Voz de Galicia prefers human-interest frames more frequently. Conclusions: The editorial line of both media is reflected in the politicization of issues such as the allocation of responsibilities. El País stands out for using a deeper journalistic content and La Voz de Galicia uses a more superficial one with a tendency to sensationalism.